Moralische Pluralität und kulturelle Vielfalt in der Gesundheitsversorgung: Medizinische, rechtliche und ethische Perspektiven - Duttge, Gunnar; Simon, Alfred; Böhme, Hendrik; Coors, Michael; Wallner, Jürgen; Weilert, A. Katarina; Neitzke, Gerald; Bobbert, Monika (Universitätsverlag Göttingen, 2025)
The ideal of the “therapeutic partnership” is characterized by a consensus of assessments on the meaningfulness of therapeutic options in a doctor-patient relationship. However, the reality of life in society reveals a pluralism of moral concepts of rightness and convictions of conscience, often caused by different cultural or social influences. These are not only based on the part of patients and their relatives, but also on the part of those providing treatment and the - possibly denominationally bound - institutions. The law is caught in the disruptive field of tension between the demand for standardization for the sake of care security and the recognition of highly personal freedom, especially for minorities.